Antinociceptive Activity of Haruan (Channa Striatus) Traditional Extract - Abdul Ghani, Zuleen Delina Fasya (2010)
The objectives of this study were to determine the amino acid and fatty acid composition of Haruan Traditional Extract (HTE), to elucidate the mechanism responsible for its antinociceptive activity and to clarify the relationship between the presence of amino acids and fatty acids with the expected activity. The HTE was obtained by steaming fresh fillet of Channa striatus with pressure cooker at 100oC, for 3 hrs after 1 hr of seasoning process. For the antinociceptive activities of HTE at different concentration, the extracts were purified, filtered and prepared in concentrations of 100 (stock solution), 50 and 10% dilution in distilled water and subjected to the antinociceptive studies. The antinociceptive activities of HTE was done on different molecular weight, where some of the extract was subjected to the centrifugation-filtration process with Ultraspeed Centrifuge for 7k G in 3 hr using Vivaspin Polythersulfone Membrane with different pore size (3k, 5k, 10k and 30k NMWL) while part of it would be kept in non-filtered conditions / stock solution prior to the antinociceptive assays. Lastly, for the elucidation of the involvement of opioid receptor in HTE antinociceptive activities, the antinociceptive action of the extract with the highest antinociceptive activity resulted from the prior study were tested against naloxone in all antinociceptive assays in a bid to further elucidate probable mechanisms of antinociception. In all of the above-mentioned studies were involved the use of 0.6% acetic acid-induced abdominal constriction, 5% formalin-induced paw-licking, and 50oC hot plate test in rodent to evaluate the HTE antinociceptive activities. For the determination of amino acid and fatty acid the stock solution HTE was run into the High Performance Liquid Chromatography (HPLC) and Gas Chromatography (GC), respectively. All data obtained were analyzed using the One-Way Analysis of Variance (ANOVA) followed by Dunnet test with P<0.05 as the limit of significance. From the data obtained, the HTE was found to contain major amino acid cysteine, histidine, glutamic acid, glycine and aspartic acid. In addition, the HTE was found to have a high myristic acid followed by palmitic, arachidonic, linolenic and oleic acid. The HTE exhibited oncentration /dosage-dependent manner significant antinociceptive activity (P<0.05). On the other hand, at different molecular, HTE showed the size-dependent in abdominal constriction, hot plate and first phase of formalin test. HTE also were showed to have an involvement of central antinociceptive mechanism when tested against the naloxone. As a conclusion, the HTE contains all the important amino acids and fatty acids and possesses the antinociceptive activities. Thus, proved the traditional claimed for reducing pain, inflammation and promote wound healing properties.